Enhancing Recycled Asphalt Mixtures Through Morphological Analysis and Rejuvenator Effects - Adnan (Jurnal Civil Engineering Study, 2025)
Recycled Asphalt Pavement (RAP) is a naturally useful and cost-effective elective for virgin black-top assets for asphalt development. This ponder explores how morphological parameters such as discuss voids, rejuvenator dissemination, and film thickness influence the adequacy of RAP blends. Waste Engine Oil (WEO) was tried as a rejuvenator in shifted amounts (3%, 6%, 9%, and 12%) to recuperate the viscoelastic qualities of ancient black-top cover. The rheological and physical characteristics of RAP and virgin folios were inspected to decide the adequacy of rejuvenators. The discoveries appear that the reasonable application of rejuvenators may enormously make strides in the life span and mechanical execution of RAP blends, making them a reasonable choice for maintainable asphalt development.